2013
DOI: 10.29052/ijehsr.v1.i2.2013.93-97
|View full text |Cite
|
Sign up to set email alerts
|

Medical Students Bearing Mental Stress Due to their Academic Schedule

Abstract: Medical education is inherently stressful and demanding. Overwhelming burden of information leaves a minimal opportunity to relax and recreate and sometimes leads to serious sleep deprivation. Environmental and social circumstances play a major role in the onset of stress-related diseases. Developing countries share the heavy burden of social and economic challenges. A number of factors-including academic pressure, workload, financial concerns, sleep deprivation, exposure to patients' suffering and deaths, stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 50 publications
1
1
0
Order By: Relevance
“…[16][17][18][19][20] Similar findings were obtained in this study. Though students reported stressors in every domain, maximum was seen in academic domain where 71.7% of the students reported that a constant need to do well was distressing them, while 70.8% reported vast amount of content to be learned and 65.4% reported heavy workload as the cause for depression.…”
Section: Depressionsupporting
confidence: 81%
“…[16][17][18][19][20] Similar findings were obtained in this study. Though students reported stressors in every domain, maximum was seen in academic domain where 71.7% of the students reported that a constant need to do well was distressing them, while 70.8% reported vast amount of content to be learned and 65.4% reported heavy workload as the cause for depression.…”
Section: Depressionsupporting
confidence: 81%
“…Sleep quality constitute a significant indicator of students’ physical and/or psychological wellbeing as well as their abilities to cope with stressful situations and multiple required tasks [16] , [17] , [18] . After COVID-19 outbreak in Tunisia, medical students became confronted with an unpredicted stressful situation, rather than the habitual academic pressure, which is home confinement for several weeks.…”
Section: Discussionmentioning
confidence: 99%
“…5(a). The linear variation of UV absorption indicates that the absorption coefficient near the absorption edge is exponential in nature and obeys the empirical Urbach rule given by [17,18], = exp ℎ ΔΕ 5 where is a the Urbach energy and β is the inverse slope of the ln α ~ ℎ plot. This exponential behaviour is due to the band tails associated with the valence and conduction band extended into the band gap.…”
Section: Solid State Science and Technology Towards An Immersive Brea...mentioning
confidence: 99%